2010
DOI: 10.1111/j.1095-8312.2010.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for ecology in male mate discrimination of immigrant females in Calopteryx damselflies?

Abstract: Sexual selection against immigrants is a mechanism that can regulate premating isolation between populations but, so far, few field studies have examined whether males can discriminate between immigrant and resident females. Males of the damselfly Calopteryx splendens show mate preferences and are able to force pre-copulatory tandems. We related male mate responses to the ecological characteristics of female origin, geographic distances between populations, and morphological traits of females to identify facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…The ontogenetic change in male mate preferences occurs most likely because of learned mate recognition, which in this case does not result in a preference for one of the morphs, but rather a loss of an innate preference for androchrome females. The importance of male mate choice in insects has received significant support over the last years [45-47] and learning in this context can be an important component of mate preference formation, where preferences are often influenced by the phenotypic variation that individuals encounter throughout their lives [43]. The modification of male morph preferences observed in our study has parallels to that observed in invertebrate predators that learn to avoid certain colours of aposematic prey [48,49].…”
Section: Resultssupporting
confidence: 72%
“…The ontogenetic change in male mate preferences occurs most likely because of learned mate recognition, which in this case does not result in a preference for one of the morphs, but rather a loss of an innate preference for androchrome females. The importance of male mate choice in insects has received significant support over the last years [45-47] and learning in this context can be an important component of mate preference formation, where preferences are often influenced by the phenotypic variation that individuals encounter throughout their lives [43]. The modification of male morph preferences observed in our study has parallels to that observed in invertebrate predators that learn to avoid certain colours of aposematic prey [48,49].…”
Section: Resultssupporting
confidence: 72%
“…Studies on niche diversification have primarily concentrated on adults of the genus Calopteryx (Wellenreuther et al 2010a;Wellenreuther et al 2012), Enallagma (McPeek et al 1996McPeek and Peckarsky 1998;Brown et al 2000;Turgeon and McPeek 2002;Siepielski et al 2010) and Ischnura (Wellenreuther et al 2011;S anchez-Guill en et al 2012), while a lot less is known about larval ecology. Comparatively, more attention has been given to the role of nonecological selection on reproductive traits (see Box 2 for a summary of damselfly reproductive biology), including in Argia (Paulson 1974), Calopteryx (Svensson et al 2007;Svensson et al 2010Svensson et al , 2014Tynkkynen et al 2008b;Wellenreuther et al 2010a,b), Enallagma (Robertson and Patterson 1982;McPeek 1995;McPeek et al 2008McPeek et al , 2009McPeek et al , 2011, Ischnura (Paulson 1974;Monetti et al 2002;S anchez-Guill en et al 2005S anchez-Guill en et al , 2011aS anchez-Guill en et al 2012S anchez-Guill en et al , 2013a and Nehalenia (Van Gossum et al 2007).…”
Section: Criteria For Genera Selection and Phylogenetic Relationshipsmentioning
confidence: 99%
“…Studies on niche diversification have primarily concentrated on adults of the genus Calopteryx (Wellenreuther et al. ; Wellenreuther et al. ), Enallagma (McPeek et al.…”
Section: Criteria For Genera Selection and Phylogenetic Relationshipsmentioning
confidence: 99%